- Correlation between 25-hydroxyvitamin D Level of Lactating Mothers and Bone Mineral Density of Infants and Analysis of Risk Factors: - - Wu, Huiwen (Journal of Medical Biochemistry, 2024)
Abstract: it was to demonstrate the influencing factors of infant bone mineral density(BMD) and its correlation with serum 25-hydroxyvitamin D (25-(OH)D) in nursing mothers. 200 children aged 0 ~ 1 years were rolled into normal group (n=120) and abnormal group (n=80) regarding the results of ultrasound BMD examination. The sunshine duration of infants with different BMD and 25-(OH)D, calcium and phosphorus levels of nursing mothers were analyzed, and univariate and multivariate analyses of BMD were implemented. The results revealed that the sunshine duration and serum 25-(OH)D level of nursing mothers in abnormal group were inferior to those in normal group (P
Keywords: Infants; Bone mineral density; Serum 25-hydroxyvitamin D (25-(OH)D); Sunshine duration; Influencing factors